Spatial Correlation Analysis of 3D MIMO Array - Chang Mu; Junliang Yao; Zhenhe Cai (Dianxin kexue)
The spatial correlation of 3D MIMO arrays was investigated. First, the accurate channel model for 3D-MIMO in global coordinate system was presented. Based on the channel model, the closed-form formula of spatial correlation coefficient for different array position under Laplace power angle spectrum（PAS）distribution was derived. Finally, three examples were provided to confirm the validity of our analysis, and the reasons for generating spatial correlation were obtained.